2006
DOI: 10.1158/1541-7786.mcr-05-0193
|View full text |Cite
|
Sign up to set email alerts
|

Δ9-Tetrahydrocannabinol-Induced Apoptosis in Jurkat Leukemia T Cells Is Regulated by Translocation of Bad to Mitochondria

Abstract: Plant-derived cannabinoids, including #9-tetrahydrocannabinol (THC), induce apoptosis in leukemic cells, although the precise mechanism remains unclear. In the current study, we investigated the effect of THC on the upstream and downstream events that modulate the extracellular signal-regulated kinase (ERK) module of mitogen-activated protein kinase pathways primarily in human Jurkat leukemia T cells. The data showed that THC down-regulated Raf-1/mitogenactivated protein kinase/ERK kinase (MEK)/ERK/RSK pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 65 publications
5
59
2
Order By: Relevance
“…Studies from our laboratory and others have established that THC and other cannabinoids can effectively suppress inflammatory response (Karsak et al, 2007;Michalski et al, 2007;Hegde et al, 2008;Jamontt et al, 2010). Moreover, we have also previously shown that THC can inhibit malignancies of the immune system (McKallip et al, 2002a;Lombard et al, 2005;Jia et al, 2006). Thus, cannabinoid receptors may be an excellent target candidate for use in graft-versus-leukemia treatment as well.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Studies from our laboratory and others have established that THC and other cannabinoids can effectively suppress inflammatory response (Karsak et al, 2007;Michalski et al, 2007;Hegde et al, 2008;Jamontt et al, 2010). Moreover, we have also previously shown that THC can inhibit malignancies of the immune system (McKallip et al, 2002a;Lombard et al, 2005;Jia et al, 2006). Thus, cannabinoid receptors may be an excellent target candidate for use in graft-versus-leukemia treatment as well.…”
Section: Discussionmentioning
confidence: 76%
“…This is also the reason we have seen that agents such as THC that activate both CB1 and CB2 are more effective than CB1 or CB2 select agonists for causing immunosuppression. We have previously shown that activation of T cells with THC triggers molecular signaling involving down-regulation of Raf-1/mitogen-activated protein kinase/extracellular signalregulated kinase kinase/extracellular signal-regulated kinase/ribosomal kinase pathway, leading to translocation of Bad to mitochondria and this signaling can be inhibited by both CB1 or CB2 antagonists (Jia et al, 2006). Thus, we believe that the downstream signaling events after cannabinoid receptor activation are similar.…”
Section: Discussionmentioning
confidence: 82%
“…Although anticancer studies involving CANNs have rightly concentrated on cancers of the brain (21), a number have focused on their efficacy in leukaemias (13,22,23). Earlier investigations studied the action of THC alone in leukaemia, but limitations to the dosages that could be used in patients due to the psychoactivity associated with its use, made THC unattractive.…”
Section: Discussionmentioning
confidence: 99%
“…259 THC-induced apoptosis in Jurkat leukemia T cells was found to be regulated by translocation of Bad to mitochondria. 260 Exposure of leukemia cells to CBD led to CB2-mediated reduction in cell viability and induction in apoptosis (although CBD is considered not to bind to either CB1 or CB2 receptors). It is noteworthy that CBD exposure led to an increase in reactive oxygen species (ROS) production as well as an increase in the expression of the NAD(P)H oxidases Nox4 and p22(phox).…”
Section: Cancermentioning
confidence: 99%